2016
DOI: 10.1038/srep32541
|View full text |Cite
|
Sign up to set email alerts
|

miR-564 acts as a dual inhibitor of PI3K and MAPK signaling networks and inhibits proliferation and invasion in breast cancer

Abstract: Dysregulation of PI3K and MAPK pathways promotes uncontrolled cell proliferation, apoptotic inhibition and metastasis. Individual targeting of these pathways using kinase inhibitors has largely been insufficient due to the existence of cross-talks between these parallel cascades. MicroRNAs are small non-coding RNAs targeting several genes simultaneously and controlling cancer-related processes. To identify miRNAs repressing both PI3K and MAPK pathways in breast cancer, we re-analyzed our previous miRNA mimic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 85 publications
2
37
0
Order By: Relevance
“…When taking all of these considerations together, our data suggest that silencing any two of the three target genes is better than silencing any one, and that silencing all three genes is better than silencing any two. Similar multi‐component strategies have been successfully employed to treat several other types of cancer, suggesting that LNPs could have broad applicability for cancer treatment.…”
Section: Discussionmentioning
confidence: 95%
“…When taking all of these considerations together, our data suggest that silencing any two of the three target genes is better than silencing any one, and that silencing all three genes is better than silencing any two. Similar multi‐component strategies have been successfully employed to treat several other types of cancer, suggesting that LNPs could have broad applicability for cancer treatment.…”
Section: Discussionmentioning
confidence: 95%
“…In terms of cell activation and proliferation, the PI3K/Akt/mTOR signaling pathway has been highlighted to play an important role in vital cell functions including cell growth, proliferation, differentiation and survival (39). Its hyper-activation can lead to excessive tumor cell proliferation, inhibition of apoptosis, angiogenesis, invasion and metastasis (40)(41)(42). For our part, we suggest that MET treatment may play a noticeable role in modulating cell signaling activation related to PI3K/Akt/mTOR pathways in breast cancer cells, that corroborates recent reports (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Leptin was reported to promote the breast cancer cells EMT by activating the PI3K/AKT signaling pathway . miR‐564 could directly target the AKT2 and inhibit the PI3K/AKT pathway, and further inhibit the EMT process, proliferation, and invasion of breast cancer . Xie et al found that FYN was transcriptionally regulated by FOXO1, and mediated FGF2‐induced EMT through both the PI3K/AKT and ERK signaling pathways .…”
Section: Discussionmentioning
confidence: 99%